2021
DOI: 10.3847/1538-3881/ac0af8
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the X-Ray Emission of Intermediate-mass Pre-main-sequence Stars

Abstract: We use X-ray and infrared observations to study the properties of three classes of young stars in the Carina Nebula: intermediate-mass (2-5 M e ) pre-main-sequence stars (IMPS; i.e., intermediate-mass T Tauri stars), late-B and A stars on the zero-age main sequence (AB), and lower-mass T Tauri stars (TTS). We divide our sources among these three subclassifications and further identify disk-bearing young stellar objects versus diskless sources with no detectable infrared (IR) excess emission using IR (1-8 μm) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…Many of them are A-and late-B type stars. Our findings of diminishing X-ray emission levels are consistent with the well known fact that such stars lack both the convection zones driving magnetic activity in lower-mass stars and the strong radiation driven stellar winds with shocks responsible for X-ray emission in O-and early Btype stars (e.g., Güdel & Nazé 2009;Stelzer et al 2009;Drake et al 2014;Nuñez et al 2021). Occasionally, the X-ray emission is detected from some of such systems and probably is not produced by the massive primary, but rather by lower mass unresolved secondaries in multiple systems (Stelzer et al 2005(Stelzer et al , 2009.…”
Section: Discussion: Interior Dynamos and Surface Activitysupporting
confidence: 91%
“…Many of them are A-and late-B type stars. Our findings of diminishing X-ray emission levels are consistent with the well known fact that such stars lack both the convection zones driving magnetic activity in lower-mass stars and the strong radiation driven stellar winds with shocks responsible for X-ray emission in O-and early Btype stars (e.g., Güdel & Nazé 2009;Stelzer et al 2009;Drake et al 2014;Nuñez et al 2021). Occasionally, the X-ray emission is detected from some of such systems and probably is not produced by the massive primary, but rather by lower mass unresolved secondaries in multiple systems (Stelzer et al 2005(Stelzer et al , 2009.…”
Section: Discussion: Interior Dynamos and Surface Activitysupporting
confidence: 91%
“…The cooler predecessors of the Herbig Ae/Be stars are occasionally referred to as Intermediate-Mass T Tauris (IMTTs). The defining difference between both groups is arbitrary in the literature and different thresholds in spectral type and mass have been used (e.g., Calvet et al 2004;Povich et al 2016;Villebrun et al 2019;Nuñez et al 2021;Valegård et al 2021). Valegård et al (2021) compiled most IMTTs within 500 pc, describing the general properties of a sample of 49 sources.…”
Section: Introductionmentioning
confidence: 99%
“…These statistics, summarised in Table 2, 2021) with mass determinations. However, other less famous objects of the class do exist in the literature, like the recently proposed 58 Herbig Ae/Be sources from the LAMOST survey (Shridharan et al 2021;Zhang et al 2021), the 13 proposed Herbig Ae/Be stars in the Small Magellanic Cloud (Keller et al 2019), or the 77 IMTTs found in the Carina Nebula (Nuñez et al 2021).…”
Section: General Remarksmentioning
confidence: 99%
“…The defining difference between both groups is arbitrary in the literature and different thresholds in spectral type and mass have been used (e.g. Calvet et al 2004;Povich et al 2016;Villebrun et al 2019;Nuñez et al 2021;Valegård et al 2021). Valegård et al (2021) compiled most IMTTs within 500 pc, describing their general properties of a sample of 49 sources.…”
Section: Introductionmentioning
confidence: 99%